2013
DOI: 10.2147/ndt.s44248
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of depression in patients with systemic lupus erythematosus: a cross-sectional study

Abstract: ObjectiveThe purpose of this study was to estimate the prevalence and examine the predictors of depression in patients with systemic lupus erythematosus (SLE).MethodsThis cross-sectional study was conducted in the rheumatology clinic of a university hospital. All SLE patients that met the revised American College of Rheumatology (ACR) classification were included in the study. Sociodemographic data and medications were recorded. Disease activity for SLE was assessed with the Mexican-SLE Disease Activity Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 33 publications
6
31
3
7
Order By: Relevance
“…Chronic pain can independently contribute to the pathogenesis of depression, through elevation of inflammatory cytokines IL‐1β, IL‐6, and TNF‐α . Here, we review the prevalence and characteristics of depression, and its correlation to the levels of inflammatory cytokines and disease activity among different CTD (Tables and ).…”
Section: Depression In Connective Tissue Diseasesmentioning
confidence: 99%
“…Chronic pain can independently contribute to the pathogenesis of depression, through elevation of inflammatory cytokines IL‐1β, IL‐6, and TNF‐α . Here, we review the prevalence and characteristics of depression, and its correlation to the levels of inflammatory cytokines and disease activity among different CTD (Tables and ).…”
Section: Depression In Connective Tissue Diseasesmentioning
confidence: 99%
“…The prevalence of depression ranged from 4% in Canada to 66.3% in Egypt among individuals with RA [28,43], 4.1% in Taiwan to 61.3% in Brazil among individuals with OA [88,90], and from 15% in China (Mainland) to 45.2% in the Thailand among individuals with SLE [114,139]. Further, international studies examining the prevalence of depression among individuals with arthritis also reported substantial variations [140].…”
Section: Prevalence Of Depression Among Individuals With and Withomentioning
confidence: 99%
“…This hypothesis was first proposed based on the high incidence of immunological abnormalities in patients diagnosed with major depression compared to the general population (Herbert and Cohen, 1993) and the development of depression in patients with no prior history of affective disorders undergoing immunotherapy (Raison et al, 2006). Subsequent studies have begun to establish a link between depression and inflammatory conditions such as auto-immune diseases, multiple sclerosis, cardiovascular diseases, diabetes, obesity, as well as with others clinical conditions linked with inflammation such as asthma and allergies (Maneeton et al, 2013;Marrie et al, 2009;Brydon et al, 2009;Walker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%